Pelatihan Pengajaran Dengan Metode Scramble Dalam Menghafal Al-Qur’an dan Tajwid di TPQ Anisa Rumbuk Timur - Anisa, Zainiya; Dina Oktaviana,; Farida Ariany,; Ahmad Zainul Irfan, (Jurnal Dedikasi Madani, 2025)
Abstract The use of the scramble method in learning is important in making learning activities more interesting, interactive, and effective. With the ability to create interesting and easy-to-understand learning media, teachers can increase student engagement and motivation, facilitate material understanding, and save time and resources. TPQ Anisa, Rumbuk Timur Village, Sakra District, East Lombok Regency, has never conducted teaching method training for teachers. The lack of life skills in designing their methods is one of the obstacles in running an effective and interesting classroom atmosphere. Thus, TPQ Anisa is suitable as a training place for the scramble teaching method for the Qur'an memorization and tajwid program for teachers. The purpose of this training is to improve the skills of TPQ Anisa teachers in teaching using the scramble method as a step towards creating creative and interactive learning media. Thus, it is expected to improve the quality of learning and student engagement.